Chemical Property of the Fly Ash Collected at an Incinerator and its Effects on Near Ambient Particles - Chang-Jin Ma; Gong-Unn Kang (Asian Journal of Atmospheric Environment, 2019)
It is crucial for understanding the characteristics of fly ash, emitted from the incinerator of municipal solid waste, to properly diagnose its impact on air quality and human health. In this study, to precisely describe the chemical property of the fly ash and its effects on near ambient particles, an intensive measurement was conducted. Fly ash was collected in dry condition from the downstream of a bag filter dust collector which is installed at an incinerator located in Iksan City, Korea. Sampling of ambient particles was carried out at both near and far away sites from an incinerator. Elemental analyses of the pretreated samples were subsequently performed by a Particle Induced X-ray Emission (PIXE) and a Scanning Electron Microscope (SEM) equipped with an Energy Dispersive X-ray Detector (EDX). Moreover, in order to estimate the residents’ exposure to the fly ash and the effect of fly ash on the near ambient particles, Gaussian plume model was carried out. The high content of soluble S, Cl, K, and Ca in fly ash were detected. Small quantities of heavy elements including Zn, Br, and Pb were also detected in the water-soluble fraction. The scattering plots drawn by the ratios of Z/Zn (i.e., the ratio of mass concentration of each element (Z) to that of zinc) of ambient PM2.5 and that of fly ash reveal a good relationship regardless of the distance from an incinerator. A ternary plot drawn by the wt% concentrations of Na, K, and Cl in the individual ambient particles and fly ash powders indicates that a small portion of the fine and coarse ambient particles was directly influenced by the fly ashes. Modeling evaluation of fly ash diffusion suggests that the air quality at the incinerator nearby areas, especially 1.5 km points, was strongly influenced by the air pollution materials emitted from an incinerator.